Performance of lightweight hemp concrete with alkali-activated cenosphere binders exposed to elevated temperature. (10th November 2019) - Kristombu Baduge, Shanaka; Mendis, Priyan; San Nicolas, Rackel; Nguyen, Kate; Hajimohammadi, Ailar
Highlights: The density, age, temperature and type of cenosphere affects the performance. FTIR analysis showed that at binders perform differently at higher temperatures. Mechanical properties decrease with the time due to failure in shell structure of cenosphere. Cenosphere binder can be a sustainable alternative for lime binder in hemp concrete. Abstract: This study investigates the performance of three different types of cenosphere as a lightweight supplementary cementitious material for alkali-activated binder for lightweight carbon-negative hemp-concrete for non-load bearing applications. Mechanical performance of hemp concrete exposed to three temperatures, room temperature (RT), 300 °C and 600 °C are studied using mechanical testing, thermogravimetric analysis (TGA) and Fourier-transform Infrared Spectroscopy (FTIR). Hemp concrete with cenosphere binder remained its integrity and showed a lower load carrying capacity even after exposure to elevated temperatures. Compressive strength capacity and elastic modulus of the samples reduced with the increase of temperature and shows the composite material is more suitable for non-load bearing application considering its mechanical behavior and fire requirements. The density, age, and type of cenosphere showed effects on mechanical properties at room temperature and elevated temperatures. The study shows that alkali activated cenosphere binders can potentially be a sustainable alternative to the lime binder.